The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12094-017-1804-1
|View full text |Cite|
|
Sign up to set email alerts
|

Curative radiation therapy for very elderly bladder cancer patients with localized disease

Abstract: RT with contemporary 3D-CRT techniques after TURBT for MIBC in elderly patients is feasible and well-tolerated. Achieving a maximal response and shortening the total radiation treatment time may improve outcomes and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Preliminary studies have reported a good tolerance in older cancer patients treated with chemotherapy and radiotherapy [43,44]. For instance, there were no difference in survival or grade 3-4 toxicity between older head and neck cancer patients (median age 74, range 70-90) and younger ones treated with concurrent chemoradiation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have reported a good tolerance in older cancer patients treated with chemotherapy and radiotherapy [43,44]. For instance, there were no difference in survival or grade 3-4 toxicity between older head and neck cancer patients (median age 74, range 70-90) and younger ones treated with concurrent chemoradiation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy and chemotherapy may be provided for patients with BCs that may recur. 3 Invasive BC is a tumor between benign and malignant BCs, which BC cannot be completely resected because of its important adjacent structure, and is prone to recurrence after operation. 4 In recent years, the emergence of small RNA has provided a new way for us to study the pathogenic genes of BC.…”
Section: Introductionmentioning
confidence: 99%